Relacionalidade no Direito Tributário: capacidade contributiva no contexto da coordenação de proposições prescritivas - Rocha, Pedro Felipe de Oliveira (2024)
Since the beginning of the 20th century, natural and social sciences have been in the midst of a scientific-philosophical transition – the relational turn. In the philosophical field, it aims a replacement of the ontological premise, abandoning substantialism to adopt relationalism. In the scientific sphere, it aims the construction of knowledge based on this new philosophical basis. Considering that the science of law has bypassed the relational turn, this work takes the first step towards that movement with the development of the initial ideas of legal relationalism, an ontological theory that sets relation as the category with primacy in the constitution of the reality of positive law. Under this philosophical premise, this thesis performs a controlled experiment, studying contributive capacity as a relational phenomenon par excellence, a true condition of possibility for the national tax system. In carrying out this task, the hypotheticodeductive method and linguistic-relationalist constructivism were adopted. It was concluded that the adoption of legal relationalism enhanced the scientific analysis of contributive capacity, enabling the development of an innovative perspective and contributing to the advancement of the science of tax law.